Maternal Erotic Transferences and the Work of the Abject. (February 2022) - Celenza, Andrea
Kristeva's profound and comprehensive understanding of maternal eroticism allows us to examine the ways in which a negative maternal transference, structured through the work of the abject, can be viewed as a maternal erotic transference in its de vitalizing form. Through the use of a clinical case, the re vitalizing experiences of maternal eroticism within analytic process facilitate the emergence of a maternal erotic transference in its vitalizing form. The lack of erotic dimensions in maternal transferences, it is argued, may be viewed as present absences, and the development of a positive maternal erotic transference as an achievement . André Green's visual-spatial metaphor of foreclosed space is extended as an imploding force wherein abject signifiers do their devitalizing work. In contrast, the usable space of a healthy psychoanalytic process is viewed as the envelope around which abject signifiers emerge, becoming available for psychoanalytic work. A transformation related to the author's experiences with her dying mother is shown to have expanded her containing capacities, including new areas of patience and receptivity. These dynamics are placed within the context of a multiverse conception of maternal eroticism, including the analyst's disciplined receptivity, viewed as an eternal signifier of the maternal.